The Effect of Artificial Intelligence on Public Service Quality in the Tax Service Sector - La Ilman; M. Umar Kelibia; Ide Raunas; Harmoko Harmoko; Raden Giri; Pandri Zulfikar (International Journal of Business and Quality Research, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed public sector operations, particularly in the tax service sector. This study aims to analyze the effect of AI on public service quality, focusing on efficiency, accuracy, responsiveness, and taxpayer satisfaction. Using a qualitative approach through a literature review of recent academic studies (2015–2025), this research examines how AI technologies such as machine learning, predictive analytics, and chatbots contribute to improving tax administration services. The findings indicate that AI enhances service quality by automating administrative processes, reducing human error, and enabling faster and more reliable service delivery. AI-driven systems also support data-driven decision-making, which improves transparency and accountability in tax administration. Furthermore, the use of AI-based digital platforms increases accessibility and user satisfaction by providing real-time assistance and personalized services. However, the implementation of AI also presents challenges, including data security risks, system reliability issues, and ethical concerns such as algorithmic bias and lack of transparency. These challenges highlight the need for robust governance frameworks and continuous system evaluation. Overall, AI has a significant positive impact on public service quality in the tax sector, provided that its implementation is supported by appropriate infrastructure, human resources, and regulatory policies. Keywords: Artificial Intelligence; Public Service Quality; Tax Services; E-Government